Numbers that Matter: Right to Health and Peruvian Maternal Strategies. Issue 6 (18th August 2019) - Guerra-Reyes, Lucia
ABSTRACT: The rights to health and to culturally respectful care are inextricably linked in the documents supporting Peruvian Maternal Health Policy. Strategies of Intercultural Birthing and Maternal Waiting Houses were purported to reduce maternal deaths, while extending the right to health to marginalized indigenous women. Based on 17 months of field research in Peru, I argue that the narrow focus on achieving "good numbers" creates and sustains coercive modes of strategy applications. As a result, the on-the-ground implementation of these innovative strategies made them incompatible with right to health and culturally respectful care approaches. Abstract :